Pengermbangan LKPD Berbasis Higher Order Thinking Skills Menggunakan Canva pada Materi Kombinasi - Rahma Siska Utari; Ratu Ilma Indra Putri; Novita Sari; Encang S. Farindi; Hapsari Maharani; Naila Aqila Nur Dzakira; Nathanael Putera Rasjid Ginting (Jurnal Inovasi Matematika, 2024)
In the present era of digital technology, students are expected to possess metacognitive abilities that are closely associated with Higher Order Thinking Skills (HOTS). The significance of creating Learning and Teaching Materials (LKPD) based on HOTS to enhance the metacognitive capacities of high school students. This study is a qualitative descriptive research aimed at describing the process of generating LKPD based on HOTS using combination materials. The LKPD was created using Canva. The stages employed are the preliminary and prototyping stages. The data was gathered through the conduct of tests and conducting interviews. The participants in this study consisted of students from SMA Negeri 1 Indralaya Utara who possessed high, moderate, and low levels of mathematical proficiency. The HOTS-based LKPD, created using Canva, undergoes expert evaluation for validation in terms of content, construct, and language. The outcomes of the review are used to modify the LKPD until it is officially validated by the expert. Subsequently, the efficacy of the legitimate LKPD was assessed on the research participants. The trial results are given in a qualitative manner to assess the feasibility of using HOTS-based LKPD. This study generates Higher Order Thinking Skills (HOTS)-based Learning and Teaching Materials (LKPD) that are both valid and practical.